Transformasi Pedagogi Tradisional Pesantren di Era Digital: Analisis atas Metode Sorogan dan Bandongan Dalam Pembelajaran Kitab Tafsir Jalalain Di Pondok Pesantren Nawwir Quluubana - Taufiqul Hakim, Ircham; Akmal Varras Amrulloh; Hibbah Nurul Waliya (Al Jabiri: Jurnal Ilmiah Studi Islam, 2025)
This study is based on the limited number of studies that specifically examine the relationship between traditional pesantren pedagogical methods and the development of digital technology in the learning of tafsir texts. Previous studies have generally discussed sorogan and bandongan as classical pesantren learning methods, or addressed the digitalization of Islamic education in a broader context. However, few studies have explored how these two aspects intersect in the practice of learning Tafsir Jalalain. This study aims to analyze the transformation of the sorogan and bandongan methods in the teaching of Tafsir Jalalain at Pondok Pesantren Nawwir Quluubana, Sukorejo, Wonosobo. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews with the pesantren leader, female teachers, and students, as well as documentation of learning activities. The findings show that sorogan and bandongan remain the main methods in classical text learning. The transformation does not occur in the fundamental values of pesantren education, but in the way students prepare for and review lessons through digital media, such as digital kitab, online dictionaries, recorded lectures, and communication groups. The findings also indicate that technology functions as a supporting tool, not as a replacement for teacher authority. The theoretical contribution of this study is to offer an understanding that the transformation of pesantren pedagogy in the digital era should be viewed as a process of selective adaptation, namely preserving the core of the Islamic scholarly tradition while utilizing technology in a limited and purposeful manner.